The X Factor of Public Transport - Trankjær, Christian; Nautrup, Lars (Proceedings from the Annual Transport Conference at Aalborg University, 2011)
FleX trip, X Bus, and a political accord increase public transport patronage and efficiency. In 2009 regional and municipal governments in North Denmark passed The Public Transport Plan for North Denmark 2009‐2012, which consists of three parts: FleX trip, X Bus, and a political accord. These represent an expanded service portfolio, a daring ambition, and a political commitment, respectively.